Gambaran Implementasi Pendidikan Inklusif di Kota Mataram Dilihat dari Sikap Guru yang Mengajar - Fitriatun, Erna; Nopita, Nopita (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2017)
This study aims to find the teachersâ€™ attitude towardsinclusive education in the city of Mataram and know the largest percentage of teachersâ€™ attitudes towards inclusive education cognitively, affectively or conatively. The study was conducted on sixty-eight subjects who were taught in seven inclusive country primary schools located in Mataram city. Information on teachers’ attitudes towards inclusive education is expressed through quantitative descriptive analysis using a teacher’s attitudinal scale of inclusive education adapted from the Mahat (2008) attitudes towards inclusive education scale (MATIES) developed to measure affective, cognitive and conative aspects of an attitude, in the field of inclusive education that includes the physical, social and the curriculum. The results of this study indicated that teachers in Mataram city had a high or positive attitude or received towards inclusive education, in which 40 teachers or 59% from a total of 68 teachers were in high category with a score of â‰¥ 69 and 28 teachers or 41.2% of teachers from a total of 68 teachers were in low category. Furthermore, the highest percentage of teacher attitudes towards inclusive education was conative aspect with score 1658, then affective aspect 1536 and the lowest was cognitive aspect with score 1410.